PENGAWASAN DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA KOTA PEKANBARU TERHADAP PENGUJIAN KELAIKAN MOBIL BARANG TAHUN 2011-2012 - Belly Aprialdi; Ishak, " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
The increasing number of urban population , standard of living and well-being aswell as the provision of goods demanded the need for better transportationfacilities and can ensure the safety of the public. Means is meant a roadworthiness of vehicles operating on the road. Airworthiness of the vehicle can bemeasured by testing vehicles, motor vehicle testing itself is implemented in orderto ensure the safety, environmental sustainability , and public services. This studyaims to analyze the function of monitoring the Department of Transportation inthe city of Pekanbaru communication information airworthiness testing andtroubleshooting the vehicle owner that the vehicle does not intentionally performfeasibility testing . This research was conducted in the city of Pekanbaru, which isthe key informants in this study is Section Head of Supervision and, Head ofTechnical Implementation Vehicle unit Inspection Department of Transportation,Head of Sub Division of Administration Technical Implementation Unit of theDepartment of Transportation Vehicle Inspection, Goods and car ownersthemselves. In addition to the findings of this study is the presence of around10,268 goods vehicles were not roadworthy operating. In collecting the dataobtained from the documentation and documentation - depth interviews withinformants. Once the data is collected and then analyzed using qualitativedescriptive analysis.From the results of this study concluded that the lack of awareness of the driver /owner of the vehicle to perform feasibility testing of vehicles, as well as weakoversight functions run by the Department of Transportation in the city ofPekanbaru to communication information truck which does not test the feasibilityof the vehicle. It required an increase in motor vehicles compulsory supervisionfunction tests, both on the road and on the other by means of surveillance andpersuasive repressive action against the suspected vehicle airworthiness way.Keywords: Controlling, Coordination, and Punishment